La Communication Numérique Sur La RSO Dans Le Milieu Hospitalier - Jebari Bouchra (European Scientific Journal, ESJ, 2017)
Mainly associated with the private sector, Corporate Social Responsibility -CSR- can also play a big and important role for public organizations; regardless of their size, type, orientation(s) or mission(s), these organizations tend to pursue more and more effective initiatives in order to be socially responsible. In health sector, hospital centers are organizations where “social” is part of their basic missions, two more aspects “environmental” and “economic” can be added in order to establish CSR basis, combining these aspects through an effective communication should be at the heart of any CSR strategy. In order to study CSR content communicated online through official moroccan hospital centers’ websites and social media, we conducted this study by using different indicators from various analysis grids related to the key areas of our research (CSR, health and communication). Opting for digital communication via websites and social media can be a useful and practical way to help hospital centers be socially responsible.